Rancang Bangun Aplikasi Laporan Keuangan Berbasis Web Dengan Metode Prototype (Studi Kasus: Praktik Mandiri Bidan Nining) - Dewi Sonia Putrie; Aditya Dwi Putro; Gunawan Wibisono (Jurnal Teknologi Informasi dan Multimedia, 2026)
Technological advances in the digital era have had a significant impact on various aspects of life, including the financial reporting system. One form of this transformation is the use of web-based applications to facilitate the process of managing and presenting financial data. PMB Nining, an Independent Midwife Practice in Sukatenang Village, Bekasi Regency, still carries out manual financial reporting using books, which risks causing recording errors, physical data damage, and delays in reporting. This study aims to design and build a web-based financial reporting system using the prototype method with the Laravel framework. This approach involves users in every stage of the design so that the system developed is in accordance with their needs. In addition, system testing is carried out using the black box testing method to ensure that each function runs according to specifications. The test results show that all main features, such as user authentication, transaction recording, data validation, printing reports in PDF and Excel formats, and staff data management, function properly and achieve a 100% success rate. The system is also able to handle various types of input, both valid and invalid. The presence of dashboard and report filter features also supports a more efficient financial monitoring process. Thus, this system can be a solution to improve the accuracy and effectiveness of financial reporting at PMB Nining, while also contributing to the development of information technology in the health services sector.